Profit sharing and training - Kornelius Kraft; Julia Lang (Institute for the Study of Labor (IZA), 2011)
We analyze the impact of profit sharing on the share of workers receiving training. An effect is plausible because: 1) profit sharing is a credible commitment by firms to reward firm-specific skills acquired by formal or informal training, 2) profit sharing may reduce turnover and increase the returns to training, 3) a common payment for the whole workforce leads to peer group pressure to participate in training courses and raises incentives to help co-workers. In order to eliminate possible selectivity effects, we combine a matching approach with difference-in-differences. We identify the proportion of employees participating in profits and differentiate profit sharing according to the percentage of the workers covered by such remuneration schemes. Using German establishment data we find that profit sharing only has a significant effect on training intensity if the majority of the workforce benefits from it.
urn:nbn:de:101:1-201111303503
Keywords: C14; J33; M52; J24; 330; profit sharing; training; matching; Erfolgsbeteiligung; Weiterbildung; Bildungsverhalten; Bildungsertrag; Schätzung; Deutschland